2022
DOI: 10.1002/1878-0261.13183
|View full text |Cite
|
Sign up to set email alerts
|

TLK1‐mediated MK5‐S354 phosphorylation drives prostate cancer cell motility and may signify distinct pathologies

Abstract: Metastases account for the majority of prostate cancer (PCa) deaths, and targeting them is a major goal of systemic therapy. We identified a novel interaction between two kinases: tousled-like kinase 1 (TLK1) and MAP kinase-activated protein kinase 5 (MK5) that promotes PCa spread. In PCa progression, TLK1-MK5 signalling appears to increase following antiandrogen treatment and in metastatic castration-resistant prostate cancer (mCRPC) patients. Determinations of motility rates (2D and 3D) of different TLK1-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 76 publications
(127 reference statements)
0
28
0
Order By: Relevance
“…We previously reported that the TLK1>MK5 interaction is critical for the motility and invasive properties of all the PCa cell lines we tested, and this was most critically illustrated with the use of the specific MK5 inhibitor GLPG 0259 (in a dose-dependent manner) (28). However, as all instances of pharmacological inhibition, there was an issue of ascertaining specificityboth for MK5 and for its regulation/activation by TLK1.…”
Section: Knockdown Of Tlk1 or Mk5 Results In Reduced Motility And Inv...mentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that the TLK1>MK5 interaction is critical for the motility and invasive properties of all the PCa cell lines we tested, and this was most critically illustrated with the use of the specific MK5 inhibitor GLPG 0259 (in a dose-dependent manner) (28). However, as all instances of pharmacological inhibition, there was an issue of ascertaining specificityboth for MK5 and for its regulation/activation by TLK1.…”
Section: Knockdown Of Tlk1 or Mk5 Results In Reduced Motility And Inv...mentioning
confidence: 99%
“…IHC staining of mice lung tissue was conducted as previously described (7). Imaging was done using a 10X magnification.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
See 3 more Smart Citations